2022
DOI: 10.1017/ice.2022.172
|View full text |Cite
|
Sign up to set email alerts
|

Single-center investigation on central-line–associated bloodstream infections and blood-culture contamination during the early months of the coronavirus disease 2019 (COVID-19) pandemic

Abstract: In this retrospective cohort study, we assessed central-line–associated bloodstream infections (CLABSIs) and blood-culture contamination frequency during the first pandemic wave. Coronavirus disease 2019 (COVID-19) was significantly associated with CLABSI and blood-culture contamination. In the COVID-19 cohort, malignancy was associated with CLABSI. Black race, end-stage renal disease, and obesity were associated with blood-culture contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…0005), agency hours ( P <0.01), and percent of premium pay that were agency hours ( P <0.0001), confirming again higher numbers of travelling staff and overstretched healthcare workers during the pandemic [ 20 ]. The study from Texas also confirmed a similar association between COVID-19 and an increase in CLABSI rates [ 21 ]. The authors also noted an increase in the blood culture contamination rate.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…0005), agency hours ( P <0.01), and percent of premium pay that were agency hours ( P <0.0001), confirming again higher numbers of travelling staff and overstretched healthcare workers during the pandemic [ 20 ]. The study from Texas also confirmed a similar association between COVID-19 and an increase in CLABSI rates [ 21 ]. The authors also noted an increase in the blood culture contamination rate.…”
Section: Resultssupporting
confidence: 57%
“…, 2022 [ 31 ] COVID-19 HAI, including CLABSI, CAUTI and VAE India, Mongolia, Jordan, Lebanon, Palestine, Egypt, Turkey Retrospective data analysis International Nosocomial Infection Control Consortium (INICC) Surveillance Online System (ICUs in 7 low- and middle-income countries, LMICs, for a total of 7,775 patients) Increase in CLABSI rates (2.54 versus 4.73 per 1000 central line days) when comparing 2019 (non-COVID) versus 2020 (COVID) Increase Wang et al. , 2022 [ 21 ] COVID-19 CLABSI and blood-culture contamination rate USA Retrospective cohort study University of Texas Medical Branch (UTMB) health system COVID-19 was associated with significant increase in blood culture contamination and CLABSI rates Increase Black race, end-stage renal disease and obesity as significant risk factors Weiner-Lastinger et al. , 2022 [ 58 ] COVID-19 HAIs, including CLABSI, CAUTI, CDI and MRSA infections USA Retrospective daa analysis National Healthcare Safety Network (NHSN) database (nearly all US hospitals) Significant increase in the state-level standardized infection ratios (SIRs) for CLABSI observed in 2020 Increase …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations